Value of adenosine stress cardiovascular magnetic resonance in the evaluation of vessels supplying previously infarcted territories - Greulich, Simon; André, Florian; Buß, Sebastian Johannes; Katus, Hugo (Coronary artery disease, 2019)
Background The diagnostic performance of adenosine stress cardiovascular magnetic resonance (CMR) for the detection of significant stenosis in infarct-related arteries is widely unknown. Two different types of perfusion defects can be observed: (a) larger than or (b) equal size as scar. - We hypothesized that: (a) defect>scar predicts significant coronary stenosis, and (b) defect=scar predicts an unobstructed infarct-related artery, and (c) angina symptoms might be of additional value in stratification. - Patients and methods Patients with previous myocardial infarction referred for work-up of myocardial ischemia undergoing adenosine stress CMR were included if they had coronary angiography within 4 weeks of CMR. - Results Two hundred patients with a mean age of 66±11 years, ischemic scars (subendocardial/transmural), and a mean left ventricular ejection fraction of 53% were included. In patients with defect>scar, the positive predictive value was excellent (88%) and typical angina was reported only in the stenosis group (P=0.002). However, patients with defect=scar (with 50% showing subendocardial scar) had a prevalence of 37% for stenosis, yielding a low negative predictive value of 63%. In this group, symptoms of typical angina were independent of stenosis (P=1.0). - Conclusion A perfusion defect larger than scar is highly predictive for significant stenosis in infarct-related arteries. However, more than a third of the patients with perfusion defect of equal size as scar also showed significant coronary stenosis. As half of these patients showed still viable (subendocardial) scars, there is a high-risk of reinfarction. The addition of angina symptoms seems to increase diagnostic accuracy only in patients with perfusion defects larger than scar.